Lactococcus garvieae: An Uncommon Human Pathogen Causing Infective Endocarditis in a Valve-in-Valve Transcatheter Aortic Valve Replacement - Diego H. González-Bravo; Sergio Alegre-Boschetti; Richard Silva-Cantillo; Joshua Mercado-Maldonado; Reyshley Ramos-Márquez; Gabriel Torres-Rivera; Carlos Cortés; Josue Mercado-Crespo (Case Reports in Cardiology)
Lactococcus garvieae is a fish pathogen and an uncommon cause of human infections. There is a growing body of evidence showing its potential for causing endocarditis especially in those with prior valve surgery. In this case report, we present what we believe is the first case of endocarditis by L. garvieae affecting a valve-in-valve transcatheter aortic valve replacement that was successfully treated. Specific guidelines for the management of these patients are lacking. Our experience can contribute to the current knowledge regarding this life-threatening infection as well as to the future care of these patients. We aim to emphasize that despite not being recognized as a typical endocarditis microorganism by the Duke Criteria, the possibility of endocarditis needs to be highly entertained in patients with L. garvieae bacteremia, especially when prosthetic valves are present. Consequently, clinicians should pursue further this diagnosis with transesophageal echocardiogram and/or alternative imaging modalities (e.g., PET-CT scan and MRI) regardless of an initial negative transthoracic echocardiogram. Reaching a diagnosis of L. garvieae endocarditis led us to the decision of prolonging the antibiotic course for 6 weeks with successful results. Ultimately, surgery was not required owing to the absence of prosthetic aortic valve dysfunction and paravalvular extension of the infection.